New insights into the physicochemical properties of the human VMAT2 monoamine transporter and its mode of interaction with the neurotransmitter serotonin: An in silico analysis (Research, Society and Development, 2020)
VMAT2 are glycoproteins capable of carrying monoamines from presynaptic vesicles to synaptic clefts during neuronal firing. Present in many species of animals including, mammals, reptiles and birds, this protein has been studied extensively, however, little is known about its physical-chemical characteristics and mode of interaction with native ligands or not. In order to better characterize human VMAT2, the present study was developed in order to explore various physical-chemical, biochemical and structural parameters related to this neurotransporter through in silico tools. In this work, new and relevant ideas about the structure and its mechanism of interaction with 5-HT are presented.